Incidence and risk factors for hemorrhagic cystitis in unmanipulated haploidentical transplant recipients. Issue 6 (25th November 2015) - Ruggeri, A.; Roth‐Guepin, G.; Battipaglia, G.; Mamez, A.‐C.; Malard, F.; Gomez, A.; Brissot, E.; Belhocine, R.; Vekhoff, A.; Lapusan, S.; Isnard, F.; Legrand, O.; et al.
Abstract: Background: Hemorrhagic cystitis (HC) is a common complication after hematopoietic allogeneic stem cell transplantation (HSCT) associated with intensity of the conditioning regimen, cyclophosphamide (Cy) therapy, and BK polyomavirus (BKPyV) infection. Methods: We analyzed 33 consecutive haploidentical (haplo) HSCT recipients transplanted for hematologic diseases. Eleven patients had a previous transplant. Median follow‐up was 11 months. Graft‐versus‐host disease (GVHD) prophylaxis consisted of cyclosporine + mycophenolate mofetil and post‐HSCT Cy. Results: Thirty‐two of 33 patients achieved neutrophil recovery. Cumulative incidence (CI) of platelet recovery was 65%. CI grade II–IV acute GVHD was 44%. Twenty patients developed HC in a median time of 38 days. CI of HC at day 180 was 62%. BKPyV was positive in blood and urine of 91% of patients at HC onset. HC resolved in 18/20 patients. Factors associated with HC were previous transplant ( P = 0.01) and occurrence of cytomegalovirus reactivation before HC ( P = 0.05). Grade II–IV acute GVHD was not associated with HC ( P = 0.62). CI of day 180 viral infections was 73%. Two‐year overall survival (OS) was 50%; HC did not impact OS ( P = 0.29). Conclusion: The incidence of HC after haplo with post‐HSCT Cy is high and is associated with morbidity, especially in high‐risk patients such as those with a previous transplant history and with impaired immune reconstitution.